Pengembangan Sistem Informasi Manajemen Perpustakaan Pada Ruang Baca Fakultas Ilmu Komputer Universitas Brawijaya - I Gde Yuda Pratama; Satrio Agung Wicaksono; Mochamad Chandra Saputra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Computer Science Faculty of Brawijaya University has a reading room that provides a collection of books and various research reports used by students to learn, looking for information and references related to subjects, thesis final assignment, and some other research. The reading room has been using information systems by utilizing desktop-based information systems to serve lending and return service activities. Currently to access the information system and library services is still offline, so in the process of borrowing books, students must come to the reading room, there is no information related to the amount of availability in each book, the absence of management of fines, so that the reading room staff have difficulty in managing borrowing and return of books. So this research is done by developing a library management information system that can overcome the problem of borrowing, returns, management of mulct, and to seek information online. This research using waterfall model method in information system development that will be built and using Unified Modeling Langueage (UML) to make it easier to understand the design of the built software. Based on problem analysis resulting on 13 features system, 28 functional requirements, and 1 non-functional requirement provides an overview of the capabilities that can be done by the library management information system. The result of validation testing, the system can run well and declared valid. The results of UAT show that 100% system can be received from the side of the reading room staff and students and the results of compatibility testing, there is a critical issue that appear due to ssl or https feature is not enabled